Fused access control scheme for sensitive data sharing - Xi-xi YAN; Tao GENG (Tongxin xuebao)
In order to improve security of sensitive data sharing and distributing, fused access control scheme based on the mechanism of attribute-based encryption (ABE) and usage control (UCON) was proposed. The scheme could ensure data confidentiality in the storage, distribution process and control sensitive data sharing scope with dynamic access poli-cies. Additionally, the scheme can prevent legal users operating sensitive data illegally and prohibit privilege abuse for domain user.The results of security analysis and efficiency analysis show that fused access control scheme alleviates the administering burdens on data management server and realizes secure storage and distribution for sensitive data.